Bank Syariah Di Indonesia: Corporate Governance Dan Pengungkapan Pertanggungjawaban Sosial Islami (Islamic Social Responsibility Disclosure) - Yasmin Umar Assegaf; - Falikhatun; Salamah Wahyuni (Conference In Business, Accounting, And Management (CBAM), 2012)
The objective of this research is to provide empirical evidence of the effect of corporate governance on Islamic Social Rresponsibility Disclosure in syariah banking Indonesia. This research examines the influence of corporate governance (broad size, cross-diretorship, managerial ownership, and ownership diffusion) as independent variables, and Islamic Social Responsibility(ISR) Disclosure as the dependent variable. This research used 32 annual reports of listed companies on the website of syariah banking in Indonesia from 2007 â€“ 2010. Sample was selected using purposive sampling method. Disclosure of Islamic Social responsibility is measured by content analysis method. While multiple regression analysis was used to test the four hypotheses developed in this research. The result found that broad size is a significant variable and positive effect on the volume of the disclosure of Islamic Social responsibility, and managerial ownership is negative significant on the variation of the disclosure of Islamic Social responsibility, while cross-directorship and ownership diffusion do not affect the Islamic Social responsibility disclosure (volume or variation). The contribution of this research is provided additional knowledge for regulator, investments analysts and capital market participant as the mechanism ofÂ islamic corporate governance on Syariah Banking in Indonesia.Keywords: broad size, cross-diretorship, managerial ownership, ownership diffusion,Â Islamic social responsibility disclosure, Syariah Banking